PENGARUH SUPERVISI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DENGAN MEDIASI MOTIVASI KERJA GURU (studi pada Guru Sekolah Dasar UPT Dinas Pendidikan Kecamatan Bulu Kabupaten Rembang) - Mulyono, 12.52.02.0053; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of the principals supervision and leaderships on the performance of primary school teachers in the District Education Office Unit Bulu Rembang the motivation to work as a mediation variable. In this study population of 108 persons as respondents . With the criteria of primary school teachers, both civilian and non- civil servants in the area of ââthe District Education Office UPT Bulu Rembang. Measurements with a Likert scale of 7 (seven) alternative answers . Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Hypothesis test used in this study is regression analysis. Based on the results of the study can be summarized as follows: (i) Supervision does not affect the work motivation , (ii) Supervision of teachers has no effect on teacher performance, (iii) the principals leadership and significant positive effect on the motivation of teachers, (iv) the principals leadership influence on teacher performance, (v) teacher motivation and a significant positive effect on teacher performance, (vi) Motivation does not mediate the effect of supervision on teacher performance, (vii) Motivation does not mediate the effect of school leadership on teacher performance. Keywords : Teacher Supervision, Principal Leadership, Work Motivation and Performance Teacher.